Evaluation of ecosystem service of straw return to soil in a wheat field of China - Cui, Siyuan; Cao, Guangqiao; Zhu, Xinkai (International Journal of Agricultural and Biological Engineering, 2021)
Crop straw is an important natural resource in China because it is rich in nutrients. When returned to fields after harvests, the straw can improve soil quality and the next crop’s yield. Evaluating the economic values of the main ecological services of a farmland ecosystem while implementing the straw return technique can be a more systematic and comprehensive approach to better understand the contribution of straw return to the development of ecological agriculture. Based on the data of a field experiment established in 2010 with varying numbers of years of straw return, four ecological services, i.e., agricultural product and industrial raw materials, atmospheric regulation and purification, soil nutrient accumulation, and water conservation, were selected to estimate a net ecosystem service value (ESV) of a wheat field’s ecosystem services. Agro-ecosystem service appraisal theories were applied to estimate the economic value of each service. Results showed that straw returning improved the total ESV in the wheat system. Compared to the no straw return treatment, 1 year, 3 years, 5 years or 7 years of straw returning altered the economic value of the agricultural product and industrial raw materials (EVAIM) by –5.93% to 7.84% and improved atmospheric regulation (EVAR) by 13.66%-30.80%, soil nutrient accumulation (EVSNA) by 59.87%-233.31% and water conservation (EVWC) by 2.60%-13.26%. The total ESV of wheat plots with 1-7 years of straw returning was 3.67%-27.41% higher than that with no straw return, and the total ESV increased with the increase in years of straw return. The proportion of EVAIM out of the total ESV in this wheat field system was highest (accounted for 47.09%-55.64%), followed by EVAR and EVWC. The value of EVSNA was the lowest. However, the proportion of EVSNA was higher than that of water conservation after the fifth year of straw return. In general, the adoption of continuous straw returning in a wheat field ecosystem is ecologically valuable. The results can inform the development and implementation of ecological compensation policies involving straw return. Keywords: ecosystem service value, rice-wheat rotation, straw returning, farmland ecosystem, economic value, ecological service function DOI: 10.25165/j.ijabe.20211401.5698 Citation: Cui S Y, Cao G Q, Zhu X K. Evaluation of the ecosystem service of straw return to soil in a wheat field of China. Int J Agric & Biol Eng, 2021; 14(1): 192–198.